تسيير التنوع في الموارد البشرية كمطلب لتجنب الصراع التنظيمي - القويــزي, القايمة (Sciences de l'Homme et de la Société, 2016)
تعالج هذه الورقة البحثية اشكالية تسيير تنوع القوى العاملة في مكان العمل ودوره في تجنب الصراع التنظيمي حيث تطرقنا إلى مفهوم تسيير التنوع وأهدافه مروًا بمقارباته مع ذكر بعض الفوائد والعيوب التي قد تنشأ نتيجة لتبني هذا النمط التسييري في المؤسسات، وبعد ذلك جاء الحديث عن إدارة الصراع في المؤسسات ومجالاته وأخيرًا مستوياته، ولتحديد الدور والعلاقة الترابطية بين تسيير التنوع وتجنب الصراع أو التخفيف من حدته تطرقنا إلى الحديث عن تجنب الصراع في ظل التنوع في مكان العمل أولاً ثم مساهمة مدخل تسيير الصراعات في إنجاح ثقافة التنوع في المؤسسة ذات الطابع الدولي نزولاً من العام إلى الخاص على اعتبار أن تسير التنوع أساسًا لتجنب وخفض حدة الصراع التنظيمي.   Abstract : This paper dealt with the problematic conduct of the diversity of the workforce in the workplace and its role in avoiding organizational conflict where we dealt with the concept of management of diversity and its objectives through the approaches with mention of some of the benefits and disadvantages that may arise as a result of the adoption of this administrative in institutions pattern and then came to talk about the conflict in enterprise management and the fields and finally levels, and to determine the role and the relationship relational between the conduct of diversity and avoid conflict or mitigate touched to talk about avoiding conflict in diversity in the workplace first and then the contribution of the entrance to the conduct of the conflicts in the success of the culture of diversity in the organization of an international character down from the general to the specific on considering that going mainly to avoid and reduce unit organizational conflict.